Implementasi Peraturan Walikota Nomor 9 Tahun 2009 dalam Revitalisasi Pasar Tradisional di Kota Denpasar - I Putu Deny Adistanaya Putra; Ni Luh Made Mahendrawati; Luh Putu Suryani (Warmadewa Press, 2021)
It is important to implement traditional market revitalization, As we all know, there is unfair competition between the traditional market and the modern market. This research has two problem formulations, namely: 1) What factors influence the implementation of Revitalization of Traditional Markets in Denpasar City? 2) How is the implementation of Revitalization of Traditional Markets in Denpasar City? This research uses empirical legal research type. The data collection technique in this research is done through interviews. The implementation of this regulation has been successfully implemented, one of which is in the Badung market, Denpasar city. The purpose of this study is to identify, analyze and describe a model of cooperation between participants in the revitalization of traditional markets in the Kreneng market, Denpasar city from the perspective of good governance. Factors that influence the implementation of market revitalization legislation for the Denpasar City Government, namely: communication, resources, bureaucratic structure, character, economic, social and political environment, as well as public response, can become obstacles in the process of implementing the Kreneng market revitalization. The implementation of the traditional market revitalization program in the city of Denpasar includes human resources and funding / budget. Human resources are one of the factors that determine the success of a policy / plan.